2018
DOI: 10.1148/radiol.2018172988
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Administrations of Gadobutrol in the Pediatric Brain: No Change in T1 Signal at MRI

Abstract: Purpose To determine whether multiple doses of gadobutrol increase the T1 signal intensity in the brains of children. Materials and Methods This retrospective imaging study evaluated 91 children (median age, 5.4 years; age range, 0-17 years) with brain tumors who underwent five or more MR brain examinations at a single institution. A subgroup of 46 patients received five or more administrations of gadobutrol (0.1 mmol/kg) and underwent follow-up MRI. T1 signal intensity in the globus pallidus and dentate nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
(80 reference statements)
2
8
0
Order By: Relevance
“…Bhargava et al reported that there was no increased SI in the GP or DN with the use of at least five doses of gadobutrol, a macrocyclic GBCA. In a comparison study, Renz et al found no T 1 W SI increase with a macrocyclic agent gadobutrol, whereas they also reported SI elevation in the DN with a linear agent, gadopentetate dimeglumine.…”
Section: Discussionmentioning
confidence: 99%
“…Bhargava et al reported that there was no increased SI in the GP or DN with the use of at least five doses of gadobutrol, a macrocyclic GBCA. In a comparison study, Renz et al found no T 1 W SI increase with a macrocyclic agent gadobutrol, whereas they also reported SI elevation in the DN with a linear agent, gadopentetate dimeglumine.…”
Section: Discussionmentioning
confidence: 99%
“…Prior MRI studies of macrocyclic GBCAs included large cohorts of adult and pediatric participants who were exposed to multiple doses of MRI contrast agents (12)(13)(14)(15). However, prior studies were primarily retrospective reviews of participants who had undergone clinically indicated MRI.…”
mentioning
confidence: 99%
“…Bhargava et al . found no SI-ratio increase in the globus pallidus referenced to the corpus callosum in children with brain tumors after having received either five or more gadobutrol adminstrations (46 patients) or more than 14 administrations (6 patients) 19 . Despite that no significant increase was found in the first group, the results are comparable to our group II (bilaterally no SI-ratio increase with mean gadobutrol administrations of 7.51; pt.…”
Section: Discussionmentioning
confidence: 93%